2020
DOI: 10.1371/journal.pone.0244022
|View full text |Cite
|
Sign up to set email alerts
|

Distinct physical condition and social behavior phenotypes of CD157 and CD38 knockout mice during aging

Abstract: The ability of CD38 and CD157 to utilize nicotinamide adenine dinucleotide (NAD) has received much attention because the aging-induced elevation of CD38 expression plays a role in the senescence-related decline in NAD levels. Therefore, it is of interest to examine and compare the effects of age-associated changes on the general health and brain function impairment of Cd157 and Cd38 knockout (CD157 KO and CD38 KO) mice. The body weight and behaviors were measured in 8-week-old (young adult) or 12-month-old (mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 65 publications
0
16
1
Order By: Relevance
“…There was a significant interaction between drugs and sex ( p < 0.05). A significantly increased duration in the center of the arena of Cana treated male mice, compared to control males, suggested reduced anxiety‐related behavior, and increased willingness to explore a new environment (Shoji et al, 2016; Gerasimenko et al, 2020). None of these measures was altered in Cana‐treated female mice (Figures 6d‐h).…”
Section: Resultsmentioning
confidence: 99%
“…There was a significant interaction between drugs and sex ( p < 0.05). A significantly increased duration in the center of the arena of Cana treated male mice, compared to control males, suggested reduced anxiety‐related behavior, and increased willingness to explore a new environment (Shoji et al, 2016; Gerasimenko et al, 2020). None of these measures was altered in Cana‐treated female mice (Figures 6d‐h).…”
Section: Resultsmentioning
confidence: 99%
“…It then participates in OT release in the hypothalamus (Jin et al, 2007). Although NR supplementation did not change CD38 expression (Gerasimenko et al, 2020b), in vitro studies have shown that NAD applied to the mouse hypothalamus leads to OT release (Gerasimenko et al, 2020a).…”
Section: Nicotinamide Ribosidementioning
confidence: 99%
“…Recently, it has been shown that NAD is consumed more by an increase in CD38 in aged male mice and, thus, proposed that inhibition of CD38 or an increase in NAD may lead to a longer life span ( Tarragó et al, 2018 ; Gerasimenko et al, 2020a , b ). NAD metabolism also catalyzes the formation of cADPR ( Lee and Zhao, 2019 ).…”
Section: Functional Aspects Of the Oxytocin Transport Or Increases In...mentioning
confidence: 99%
“…Previous studies have shown behavioral deficits in constitutive CD38 KO mice, including anxiety-like behaviors, locomotor activity deficits, and altered parental and social behaviors (23, 28, 31). However, CD38 AS-cKO P10 mice did not show any of these behavioral deficits and demonstrated social memory.…”
Section: Discussionmentioning
confidence: 96%
“…Multiple studies have reported that constitutive CD38 KO mice exhibit impaired social behaviors (28)(29)(30). To investigate whether astrocytic CD38 is involved in social behavior, we conducted a three chamber social approach test of CD38 AS-cKO P10 mice, as shown in Figure 1B.…”
Section: Deletion Of Astroglial Cd38 In Postnatal Brain Impairs Socia...mentioning
confidence: 99%